1994
DOI: 10.1177/028418519403500202
|View full text |Cite
|
Sign up to set email alerts
|

Mr Spectroscopy in Clinical Research

Abstract: MR spectroscopy (MRS) offers unique possibilities for non-invasive evaluation of biochemistry in vivo. During recent years there has been a growing body of evidence from clinical research studies on human beings using lip and 'H MRS. The results indicate that it is possible to evaluate phosphorous energy metabolism, loss of neurones, and lactate production in a large number of brain diseases. Furthermore, lip and IH MRS may be particularly clinically useful in evaluation of various disorders in skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 172 publications
0
4
0
Order By: Relevance
“…17 Also, high doses of deflazacort increase muscle precursor proliferation and fusion into myotubes. 17 Nuclear magnetic resonance spectroscopy (NMR) has potential use in determining diagnosis and prognosis of disease [18][19][20] and possibly for monitoring treatment effects in vitro 21 or non-invasively in vivo. Proton NMR has been used to study biochemical aspects of skeletal muscle such as changes in fatty acid chains, membrane lipid fluidity and amino acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…17 Also, high doses of deflazacort increase muscle precursor proliferation and fusion into myotubes. 17 Nuclear magnetic resonance spectroscopy (NMR) has potential use in determining diagnosis and prognosis of disease [18][19][20] and possibly for monitoring treatment effects in vitro 21 or non-invasively in vivo. Proton NMR has been used to study biochemical aspects of skeletal muscle such as changes in fatty acid chains, membrane lipid fluidity and amino acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…MR spectroscopy enables the noninvasive measurement of biochemical information in vivo (21). In many previously published studies (22)(23)(24)(25)(26), it has been reported that liver cirrhosis can be detected with phosphorous 31 MR spectroscopy.…”
mentioning
confidence: 99%
“…MR spectroscopy provides a noninvasive measurement of biochemical information in vivo (114). Several…”
Section: Mr Spectroscopymentioning
confidence: 99%